Study on Seepage Simulation of High Pressure Grouting in Microfractured Rock Mass. (3rd February 2021) - Wang, Kai; Wang, Lianguo; Ren, Bo; Fan, Hao
Abstract : In coal mines, under high in situ stress and strong mining activity, roadway surrounding rock commonly contains large amounts of larger fractures and microfractures. Along with the large deformation and continuous rheology of the soft rock roadway, the fractures in the surrounding rock are likely to be compressed and closed, forming undeveloped microfractures, which hinder conventional grouting support methods. Based on the fluid-solid coupling between slurry seepage and microfracture deformation, a theoretical model of microfracture grouting seepage is established. A program for the analysis and calculation of microfracture grouting is developed to quantitatively describe the variation in slurry seepage distance and fracture opening. Numerical experiments are carried out to study the grouting seepage of microfractures under different grouting pressures and fracture opening conditions, and the variation rules for the spatial distribution of fracture opening and slurry seepage distance during grouting pressure are obtained. Fluid-solid coupling has a significant influence on grout seepage characteristics. The grouting pressure and the fracture opening changes are nonlinearly attenuated along the grout seepage direction.